Classroom Interaction Using IRF Pattern Carried Out by Lecturer in English Classrooms: A Discourse Analysis - Ria Ariska; Ocid Abdul Rosyid; Dewi Puspitasari (Journal of English Language Learning, 2024)
The most common pattern in classroom interaction is teacher initiates the talk in the class, learners respond to teacher talk, and teacher responds by giving corrective feedback to the learners. From this pattern it explains teacher’s dominance in the classroom interaction. Therefore, the significance of this study on whether the use of Initiation, Response and Feedback (IRF) in teaching facilitates learner-initiated communication and gives learning opportunities for learners to engage in classroom interaction. The data were taken from observation of a conversation in the classroom. The result of this study is the teaching using IRF pattern can facilitate learner-initiated communication and give opportunities for learners to engage in classroom interaction.